Carbon Emission Disclosure Viewed from Competitive Business Strategy and Environmental Performance: India's Perspective - Firmansyah; Ayu Amalia, Firda; Wicaksono, Agung Prasetyo Nugroho (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to empirically test and analyze the influence of competitive business strategy and environmental performance on carbon emission disclosure. Methodology/approach: The independent variables in this study are competitive business strategy as measured by cost leadership strategy and environmental performance as measured by implementation and ISO 14001 certificates. The population in this study are non-financial companies registered with NSE India in 2021. The sample selection in this study used a purposive sampling technique to produce 100 samples that fit and meet the criteria of 278 total population. Testing the hypothesis in this study used the statistical tool STATA 14.2 with multiple linear regression analysis techniques. Findings: The results of this study indicate that competitive business strategy has no effect on disclosure of carbon emissions, while environmental performance influences disclosure of carbon emissions. Practical implications: These research findings have an impact on stakeholders and policy makers considering Carbon Disclosure disclosure. Originality/value: This research has the latest in the form of modifications to models and objects that are relevant to the carbon emissions phenomenon.